Service Quality Gap of Care During Childbirth and Postpartum and Its Relationship with Childbirth Satisfaction - Niloofar Danehchin; Nahid Javadifar; Mina Iravani; Maryam Dastoorpoor (Shiraz University of Medical Sciences, 2023)
Background: The purpose of the present study was to evaluate the quality gap of maternity service in the labor and postpartum wards and its relationship with childbirth satisfaction.Methods: This cross-sectional study was carried out on 332 pregnant women referring to the labor and delivery wards of the two selected hospitals affiliated to Ahwaz University of Medical Sciences in 2020. Pregnant mothers were selected by convenience sampling method and data were collected using SERVQUAL and Mackey Childbirth Satisfaction Rating Scale in labor and postpartum wards. Data analysis was carried out using descriptive and inferential statistics.Results: The quality gap of maternity service in the postpartum ward (-0.35) was higher than that in the labor ward (-0.28). There was a significant difference between the mothers' expectations and perceptions in all dimensions of the SERVQUAL except for the responsiveness dimension. The highest and lowest gap in the quality of service in labor and postpartum wards was related to empathy (-0.41 and -0.48, respectively) and the responsiveness dimensions (-0.07 and -1, respectively). There was a significant inverse correlation between the gap in the empathy dimension with overall childbirth satisfaction in the labor ward. There was a correlation between empathy and overall childbirth satisfaction and the physician's satisfaction in the postpartum ward (P<0.05).Conclusion: Empathy is the most important variable affecting the quality of services provided in the maternity wards and it is necessary to improve this skill in maternity health care providers.